Non-targeted metabonomics and transcriptomics revealed the mechanism of mulberry branch extracts promoting the growth of Sanghuangporus vaninii mycelium - Huo, Jinxi; Sun, Yuqing; Pan, Meiliang; Ma, Huanyan; Lin, Tianbao; Lv, Zhiqiang; Li, Yougui; Zhong, Shi (Frontiers in Microbiology, 2022)
Sanghuangprous vaninii is a wood-inhabiting fungus, and its mycelium and fruiting body show excellent medicinal values. Mulberry is one of the major hosts of S. vaninii, however, the mechanism of mulberry affecting the growth of S. vaninii has not been reported. In the present study, a mulberry-inhabiting strain of S. vaninii was selected to explore the effects of mulberry branch extracts (MBE) on the growth of the strain. Results showed that MBE could significantly promote the growth of S. vaninii mycelium at the concentration of 0.2 g/L. After 16 days of liquid culture, the dry weight of mycelium in 0.2 g/L MBE medium was higher by three times compared with that in the control. The non-targeted metabonomic analysis of the culture medium at different culture times and concentrations was conducted to find the key components in MBE that promoted the growth of S. vaninii mycelium. Under the different concentrations of MBE culture for 10 and 16 days, 22 shared differential metabolites were identified. Next, in accordance with the peak value trend of these metabolites, HPLC-MS and liquid culture validation, four components derived from MBE (i.e. scopoletin, kynurenic acid, 3,5-dihydroxybenzoic acid and 2,4-dihydroxybenzoic acid) could significantly increase the growth rate of mycelium at the concentration of 2 mg/L. Transcriptomic and qRT-PCR analyses showed that MBE could upregulate hydrolase-related genes, such as serine–glycine–asparaginate–histidine (SGNH) hydrolase, alpha-amylase, poly-beta-hydroxybutyrate (PHB) depolymerase, glycosyl hydrolase family 61, cerato-platanin protein and Fet3, which might enhance the nutrient absorption ability of S. vaninii. Importantly, MBE could significantly increase the content of harmine, androstenedione and vesamicol, which have been reported to possess various medicinal effects. Results suggested that MBE could be an excellent additive for liquid culture of S. vaninii mycelium, and these hydrolase-related genes also provided candidate genes for improving the nutrient absorption capacity of S. vaninii.